Analisis Faktor yang Mempengaruhi Tingginya Tingkat Konsumsi Daging Sapi di Pulau Jawa Tahun 2018-2022 - Rahardiyanti, Elvina Eka (JOURNAL OF ECONOMIC AND SOCIAL EMPOWERMENT, 2024)
Abstract The purpose of the research is to analyze the influence of PDRB ADHK per capita, beef prices, and population on beef consumption on Java Island in 2018-2022 and analyze the factors that most influence beef consumption on Java Island in 2018-2022. This research uses a quantitative approach method with data collection in the form of secondary data obtained from Badan Pusat Statistik (BPS) and Sistem Informasi Pasar Online Nasional-Ternak (SIMPONI-Ternak). In the regression results, PDRB ADHK per capita has a significant effect, beef prices have an insignificant effect, and population has a significant effect on beef consumption on Java Island in 2018-2022. The factor that most influences beef consumption on the island of Java in 2018-2022 is population. Based on the results of the classical assumption test, it shows that the Common Effect Model is the most suitable model in this research. Of the 3 factors used, there are 2 factors that have a significant influence, namely GRDP ADHK per capita and population and 1 factor that has an insignificant influence, namely the price of beef.